TOXICOLOGICAL EFFECTS OF SELENIUM ON SOME PHYSIOLOGICAL PARAMETERS IN MALE RATS (RUTTUS RUTTUS) - Nabeel Mahdi abed (Basrah Journal of Veterinary Research)
This study was conducted to detect the effects of Selenium on some physiological and reproductive parameters in rats male, Twenty-four mature male rats were randomly divided into three equal groups; each group consists of eight males. First group was injected intrapretonially with 0.1 ml of normal saline for 30 consecutive days as control group, while second and third groups were intrapritonially injected with 0.1 ml of sodium Selenite at concentration (2,4 mg/kg body Wight ) of selenium for 30 days. The hematological and biochemical parameters including, red blood cells count(R.B.C), white blood cells count(W.B.C), hemoglobin concentration(Hb), package cell volume (P.C.V) , in addition to ALT and AST were performed after animals elimination . The concentration and percentage of normal and abnormal sperms were calculated after epididymis extraction. Statistical analysis reveals that significant differences (p≤0.05) in Red blood cells count, package cell volume, while WBCs count and liver enzymes ALT,AST show increase significant differences (p≤0.05) in comparison with control group . In concern with reproductive parameters, this study indicates there is significant differences in motility and activity of sperms of treated males, in comparison with control group